Inclusive Worship: Islamic Jurisprudence on Prayer Obligations for Persons with Disabilities - Setyaningrum, Ika; Defira Salma Salamah; Elsa Lysandra; Tarishah Aulia; Muhamad Parhan; Ibrahim, Adil Hasan; Mubarak, Haris (Fakultas Syariah Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2024)
This study was conducted to increase the insight of Muslims that people with disabilities have the same obligations in worship and to raise awareness of Muslims about the importance of involving all religious activities with people with disabilities without any differences. This study uses a qualitative descriptive methodology with a literature-based approach. Data collection techniques include a review of Islamic jurisprudence texts, scientific articles, and related literature that discuss the inclusion of people with disabilities in worship practices. The analysis technique used is content analysis, with a focus on the interpretation and contextualization of Islamic jurisprudence principles to address the needs and challenges faced by people with disabilities.The results of this study indicate that Islamic teachings emphasize justice and inclusivity, which require all Muslims, regardless of their physical or mental abilities, to worship. This includes the collective responsibility of the Muslim community to ensure accessibility and support for people with disabilities in carrying out their religious obligations.